Human adipose‐derived stromal/stem cells are distinct from dermal fibroblasts as evaluated by biological characterization and RNA sequencing. (3rd January 2021) - Abreu de Melo, Mariane Izabella; da Silva Cunha, Pricila; Coutinho de Miranda, Marcelo; Faraco, Camila Cristina Fraga; Barbosa, Joana Lobato; da Fonseca Ferreira, Andrea; Kunrath Lima, Marianna; Faria, Jerusa Araújo Quintão Arantes; Rodrigues, Michele Ângela; de Goes, Alfredo Miranda; Gomes, Dawidson Assis
Abstract : Human adipose‐derived stromal/stem cells (ASC) have immunomodulatory properties and the potential to differentiate into several cell lines, important for application in regenerative medicine. However, the contamination with dermal fibroblasts (FIB) can impair the beneficial effects of ASC in cell therapy. It is then essential to develop new strategies that contribute to the distinction between these two cell types. In this study, we performed functional assays, high‐throughput RNA sequencing (RNA‐Seq) and quantitative PCR (qPCR) to find new markers that can distinguish ASC and FIB. We showed that ASC have adipogenic and osteogenic differentiation capacity and alkaline phosphatase activity, not observed in FIB. Gene expression variation analysis identified more than 2000 differentially expressed genes (DEG) between these two cell types. We validated 16 genes present in the list of DEG, including the alkaline phosphatase gene ( ALPL ). In conclusion, we showed that ASC and FIB have distinct biological properties as demonstrated by alkaline phosphatase activity and differentiation capacity, besides having different gene expression profiles. Significance of the study: Although many differences between stromal stem cells derived from human adipose tissue (ASC) and human dermal fibroblasts (FIB) are described, it is still difficult to find specific markers to differentiate them. This problem can interfere with the therapeutic use of ASC. This work aimed to find new markers to differentiate these two cell populations. Our findings suggest that these cells can be distinguished by biological and molecular characteristics, such as adipogenic and osteogenic differentiation, alkaline phosphatase activity and differential gene expression profiles. The DEG were related to the regulation of the cell cycle, development process, structural organization of the cell and synthesis of the extracellular matrix. This study helps to find new cellular markers to distinguish the two populations and to better understand the properties of these cells, which can improve cell therapy.